The Effects of Noise Reduction Technologies on the Acceptance of Background Noise. - Lowery, Kristy Jones; Plyler, Patrick N. (Journal of the American Academy of Audiology, 2013)
Background: Directional microphones (D-Mics) and digital noise reduction (DNR) algorithms are used in hearing aids to reduce the negative effects of background noise on performance. Directional microphones attenuate sounds arriving from anywhere other than the front of the listener while DNR attenuates sounds with physical characteristics of noise. Although both noise reduction technologies are currently available in hearing aids, it is unclear if the use of these technologies in isolation or together affects acceptance of noise and/or preference for the end user when used in various types of background noise. Purpose: The purpose of the research was to determine the effects of D-Mic, DNR, or the combination of D-Mic and DNR on acceptance of noise and preference when listening in various types of background noise. Research Design: An experimental study in which subjects were exposed to a repeated measures design was utilized. Study Sample: Thirty adult listeners with mild sloping to moderately severe sensorineural hearing loss participated (mean age 67 yr). Data Collection and Analysis: Acceptable noise levels (ANLs) were obtained using no noise reduction technologies, D-Mic only, DNR only, and the combination of the two technologies (Combo) for three different background noises (single-talker speech, speech-shaped noise, and multitalker babble) for each listener. In addition, preference rankings of the noise reduction technologies were obtained within each background noise (1 5 best, 3 5 worst). Results: ANL values were significantly better for each noise reduction technology than baseline; and benefit increased significantly fromDNR to D-Mic to Combo. Listenerswith higher (worse) baseline ANLs receivedmore benefit from noise reduction technologies than listenerswith lower (better) baselineANLs. Neither ANLvalues nor ANL benefit values were significantly affected by background noise type; however, ANL benefit with D-Mic and Combowas similarwhen speech-like noise was present while ANL benefitwas greatest for Combowhen speech spectrum noise was present. Listeners preferred the hearing aid settings that resulted in the best ANL value. Conclusion: Noise reduction technologies improved ANL for each noise type, and the amount of improvement was related to the baseline ANL value. Improving an ANL with noise reduction technologies is noticeable to listeners, at least when examined in this laboratory setting, and listeners prefer noise reduction technologies that improved their ability to accept noise.